Combination of Antimicrobial Starters for Feed Fermentation: Influence on Piglet Feces Microbiota and Health and Growth Performance, Including Mycotoxin Biotransformation in vivo - Vadopalas, Laurynas; Ruzauskas, Modestas; Lele, Vita; Starkute, Vytaute; Zavistanaviciute, Paulina; Zokaityte, Egle; Bartkevics, Vadims; Pugajeva, Iveta; Reinolds, Ingars; Badaras, Sarunas; Klupsaite, Dovile; Mozuriene, Erika; et al. (Frontiers in Veterinary Science, 2020)
The aim of this study was to apply a microbial starter of the lactic acid bacteria (LAB) Lactobacillus uvarum LUHS245, Lctobaccilus casei LUHS210, Pediococcus acidilactici LUHS29, and Pediococcus pentosaceus LUHS183 for feed fermentation and evaluate their influence on feed acidity and microbiological characteristics. The study examined the influence of this LAB combination on piglet feces microbiota and health and growth performance. In addition, mycotoxin biotransformation was analyzed, including masking mycotoxins in feed and piglet feces samples. The 36-day experiment was conducted using 25-day-old LW/NL piglets, which were randomly distributed into two groups: control group, fed with basal diet, and treated group, fed with fermented feed at 500 g kg-1 of total feed. Compared to a commercially available LAB combination, the novel LAB mixture effectively reduced feed pH (on average pH 3.65), produced a 2-fold higher content of L(+) lactic acid, increased viable LAB count (on average 8.8 log10 colony forming units [CFU] g-1), and led to stable feed fermentation during the entire test period (36 days). Fecal microbiota analysis showed an increased number of probiotic bacteria in the treated group, particularly Lactobacillus, when compared with the control group at the end of experiment. This finding indicates that fermented feed can modify microbial profile change in the gut of pigs. In treated piglets’ blood (at day 61), the serum high density lipoprotein (HDL)-cholesterol and triglycerides (TG) were significantly higher, but the levels of T4, glucose, K, alkaline phosphatase (AP) and urea were significantly decreased (p ≤ 0.05) compared with the control group. Mycotoxin analysis showed that alternariol monomethyl ether (AME) and altenuene were found in 61-day-old control piglets’ feces and in fermented feed samples. However, AME was not found in treated piglets’ feces. Feed fermentation with the novel LAB combination is a promising means to modulate piglets’ microbiota, which is essential to improve nutrient absorption, growth performance, and health parameters. The new LAB composition suggests a novel dietary strategy to positively manipulate fermented feed chemicals and bio-safety, the piglet gut microbial ecology to reduce antimicrobials use in pig production, and increase local feed stock uses and economical effectiveness of the process.